2020
DOI: 10.5454/mi.14.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Xylanase Production by Streptomyces costaricanus 45I-3 Using Various Substrates through Submerged Fermentation

Abstract: Xylanase is an important hydrolytic enzymes with many application in several industries, but to obtain enzyme derived products is not easy. Thus, the optimization of efficient xylanases production is a great interest for biotechnological application. This study aims to determine the type of substrate, medium composition, and optimum conditions of xylanase production by S. costaricanus 45I-3. Determination of substrate type was done by growing the tested bacteria on birchwood xylan, beechwood xylan, oat spelled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
1
6
1
Order By: Relevance
“…In this study, Trichoderma viride showed its maximum xylanase activity on the eighth day of the incubation period. This result was agree with SIPRIYADI et al 202033 who reported that, the maximum activity of xylanase was obtained on the eighth day of incubation.…”
supporting
confidence: 93%
“…In this study, Trichoderma viride showed its maximum xylanase activity on the eighth day of the incubation period. This result was agree with SIPRIYADI et al 202033 who reported that, the maximum activity of xylanase was obtained on the eighth day of incubation.…”
supporting
confidence: 93%
“…Surfactants generally influence the function of proteins in cell signalling. Sodium dodecyl sulfate had a positive influence on the xylanase activities of the micro-organisms used in this work, but Gama et al [19] and Sipriyadi et al [20] reported that the addition of sodium dodecyl sulfate led to a decrease in the xylanase activities of different Streptomyces spp.…”
Section: Discussionmentioning
confidence: 63%
“…[11, 18], Streptomyces spp. [19, 20], Trichoderma spp. [21, 22] and others have been used to produce xylanase.…”
Section: Introductionmentioning
confidence: 99%
“…RCK-SC, it was found that urea (0.25% w/v) is a good inductor of the activity [48], and for polygalacturonase activity by Bacillus sphaericus (MTCC 7542), casein hydrolysate and yeast extract used together as organic nitrogen source gave best results, and ammonium chloride was found to be the most suitable inorganic nitrogen source [49]. With respect to xylanase activity, for the endoxylanase and β-xylosidase activities by Aspergillus awamori in solid-state fermentation, were higher when sodium nitrate was used as the nitrogen source, when compared with peptone, urea, and ammonium sulfate [50], too, ammonium sulphate was the most appropriate inorganic nitrogen source for xylanase production and urea increased xylanase activity slightly by Trichoderma harzianum 1073 D3 [51], on the production of xylanase by mutant strain of Aspergillus niger GCBMX-45, was observed when ammonium sulphate (0.2%) was found to be best nitrogen source for optimum enzyme production [52], for thermostable alkaline xylanase from Anoxybacillus kamchatkensis NASTPD13, among all the tested inorganic and organic nitrogen sources, ammonium sulfate, yeast extract, and peptone were found best for growth and xylanase production [53], for the activity in B. subtilis, the better inductor was ammonium sulphate [54], and by the xylanase roduction by Streptomyces costaricanus 45I-3, both source of nitrogen i.e., nitrogen ammonium sulphate and yeast extract were able to produce xylanase 8 days after incubation [55].…”
Section: Effect Of Different Nitrogen Sources On Growth Enzyme Production and Protein Secretionmentioning
confidence: 99%
“…RCK-SC, it was found that the enzyme exhibits optimum activity at temperature between 60 and 70°C [48], and for polygalacturonase activity by B. sphaericus (MTCC 7542), the optimal the temperature for bacterial growth and polygalacturonase production was 30 o C [49]. With respect to extracellular xylanase, it was reported an optimum temperature of 40°C for A. pullulans CCT 1261 [3], 50°C by crude and partially purified xylanase from A. pullulans after 24 h of incubation [43], 40°C for crude xylanase produced with A. pullulans NRRL Y-2311-1 from wheat bran [44] and B. subtilis a biobleaching agent [54], for S. costaricanus 45I-3, the optimum temperature was 28°C [55], and the xylanase production by Leucoagaricus meleagris KKU-C1 isolated from compost at pulp and paper industry, and an xylanase of P. pastoris exhibited the highest activity at 50°C [55, 57].…”
Section: Effect Of Initial Ph On Growth and Induction Of Extracellular Lytic Activitiesmentioning
confidence: 99%